Contribution of myocardium overlying the anterolateral papillary muscle to left ventricular deformation - Itoh, Akinobu (American Physiological Society, 2012)
Previous studies of transmural left ventricular (LV) strains suggested that the myocardium overlying the papillary muscle displays decreased deformation relative to the anterior LV free wall or significant regional heterogeneity. These comparisons, however, were made using different hearts. We sought to extend these studies by examining three equatorial LV regions in the same heart during the same heartbeat. Therefore, deformation was analyzed from transmural beadsets placed in the equatorial LV myocardium overlying the anterolateral papillary muscle (PAP), as well as adjacent equatorial LV regions located more anteriorly (ANT) and laterally (LAT). We found that the magnitudes of LAT normal longitudinal and radial strains, as well as major principal strains, were less than ANT, while those of PAP were intermediate. Subepicardial and midwall myofiber angles of LAT, PAP, and ANT were not significantly different, but PAP subendocardial myofiber angles were significantly higher (more longitudinal as opposed to circumferential orientation). Subepicardial and midwall myofiber strains of ANT, PAP, and LAT were not significantly different, but PAP subendocardial myofiber strains were less. Transmural gradients in circumferential and radial normal strains, and major principal strains, were observed in each region. The two main findings of this study were as follows: 1) PAP strains are largely consistent with adjacent LV equatorial free wall regions, and 2) there is a gradient of strains across the anterolateral equatorial left ventricle despite similarities in myofiber angles and strains. These findings point to graduated equatorial LV heterogeneity and suggest that regional differences in myofiber coupling may constitute the basis for such heterogeneity.